Human Microbiome and Its Medical Applications - Zhang, Yangming; Zhou, Linguang; Xia, Jialin; Dong, Ce; Luo, Xiaozhou (Frontiers in Molecular Biosciences, 2022)
Commensal microbiome is essential for human health and is involved in many processes in human body, such as metabolism process and immune system activation. Emerging evidence implies that specific changes of microbiome participate in the development of various diseases, including diabetes, liver diseases, tumor and pathogen infection. Thus, the intervention on microbiome is becoming a novel and effective method to treat such diseases. Synthetic biology empowers researchers to create strains with unique and complex functions, making engineered microbe closer for clinical applications. The aim of this review is to summarize recent advances about the roles of microbiome in certain diseases and the underlying mechanisms, as well as the use of engineered microbe in the prevention, detection, and treatment of various diseases.